The Graphical Analysis of Tooth Width Discrepancy - Christopher T.C; Freer T.J (Sciendo, 1994)
The standard tooth width ratio tables currently do not provide an overall indication of the final interdigitation of teeth. To provide a comprehensive analysis of inter-arch tooth width discrepancy, this study has developed a combination of cumulative percentage tooth width ratios and a method to visually determine the harmony betweeu maxillary and mandibular tooth widths. Mesiodistal tooth widths from the first permanent molar to the corresponding first permanent molar were measured from 60 sets of pretreatment study models which were selected consecutively. Cumulative percentage ratios relating mandibular teeth to maxillary teeth were calculated utilising the mesiodistal tooth width measurements. The 13 mean cumulative percentage ratios developed in this study were plotted on graph paper showing plus and minus two standard deviations from the mean. These ratios provide a standard from which cumulative percentage ratios obtained from any new case may be compared graphically. Deviations from the mean cnmulative percentage ratios are immccliately recognised. No simple graphical method of assessment on the final intercligitation of anterior and posterior teeth has previonsly been dcvisecl. The graphical analysis of toolh width discrepancy is invalnahle as an aicl in localising any toolh width discrepancy and ensnring that incompatihle maxillary-to-manclibnlar tooth wid ths are recognised prior to orthodontic treatment.